Information Accessibility for People with Mental Disabilities, Including Autism Spectrum Disorders - O.N. Vladimirova; N.P. Chistyakova; O.A. Miroshnichenkо (Moscow State University of Psychology and Education, 2023)
Identifying, assessing and overcoming informational barriers that arise among people with mental disabilities, including autism spectrum disorders (ASD), during communication, attract attention of all participants of the rehabilitation process. Approaches to create a unified communication space, considering the use of easy language and alternative ways of communication for people with mental disabilities, are based on the principles of the Convention on the Rights of Persons with Disabilities and the categories of the International Classification of Functioning, Disability and Health (ICF). Statistical data on increased number of people recognized as disabled for the first time due to mental disorders and autism in the Russian Federation were systematized by the staff of the St. Petersburg Institute of Advanced Medical Experts. These data substantiate the need to revise accessibility of ICF based information at two levels — individual and social ones. Authors propose to develop a unified methodology of information accessibility, considering ICF provisions, including the legal ones. Given proposals are aimed at increasing informational accessibility for people with mental disabilities, including ASD. Authors emphasize that creating a unified national standard for the use of easy language for people with mental disabilities is one of the factors guaranteeing their civil rights.